Protective Role of Pharmacologic Postconditioning with Natural Honey on Myocardial Infarction Size - M Najafi (Babol University of Medical Sciences, 2011)
BACKGROUND AND OBJECTIVE: Honey has been noticed as an effective drug more than a nutrient. There is no report regarding cardioprotective effects of postconditioning with natural honey. In the present study, effects of postconditioning by honey on myocardial infarction size in ischemic-reperfused isolated rat heart were investigated.METHODS This experimental study was performed on 42 male Wistar rats weighing 270-330 g. The rats hearts were isolated and divided into five groups including a control and four postconditioning groups (n= 8-10 in each). The hearts were subjected to 30 min regional ischemia followed by 120 min reperfusion. In the control group, the hearts were perfused by normal Krebs-Henseleit (K/H) solution throughout the experiment, however in the postconditioning groups, they were perfused with honey (0.25, 0.5 and 1%) enriched K/H solution or glucose (equivalent concentration in 1% honey solution) from 10 min before to 10 min after reperfusion. To determine the infarct size, the hearts were perfused with Evans blue dye then cut into slices and incubated with triphenyltetrazolium chloride. Finally, the infarct size was determined by computerized planimetry.FINDINGS: Perfusion of isolated hearts with honey as a postconditioning agent significantly decreased infarct size and infarcted volume in the all treated groups. In the control group, the infarct size was 47±3%, however, natural honey (0.25, 0.5 and 1%) and glucose reduced it to 26±3, 6±3, 5±2 and 21±2 %, respectively (p<0.001 for all groups).CONCLUSION: The results showed protective effects of postconditioning by natural honey against ischemia-reperfusion injuries as reduction of infarction size. Probably, antioxidant activity of honey, scavenging of free radicals and the presence of energy sources in honey composition may involve in these protective effects.